SPACE SHUTTLE : A PHOTOGRAPHIC JOURNEY - Price, Luke Wesley; Ferguson, Christopher J. (Lewes, East Sussex : Ammonite Press, 2019)
This impressive collection is arranged in thematic chapters ranging from launch pad through the launch sequence, to the missions themselves and the dramatic conclusion of the return flight. It pays tribute to the five extraordinary orbiters built by NASA: Columbia, Challenger, Discovery, Atlantis, and Endeavour, telling their story through extraordinary images from the greatest of NASA's 135 shuttle missions. Beautifully post-processed photographs capture the drama and danger of the hazardous launch sequences and vividly depict the techniques and challenges of mission tasks including space walks, in-flight maintenance work, and docking with the International Space Station. The book also collates the details of every space shuttle mission flown, including launch dates and lists of crew, alongside a gallery of the 135 exquisitely designed mission patches.
Keywords: Space Shuttle Program (U.S.) -- History -- Pictorial works; Space shuttles -- United States -- History -- Pictorial works; Space flight -- Pictorial works; Outer space -- Exploration -- Pictorial works; Illustrated works